Asthma and severity of the 2009 novel H1N1 influenza: a case-control study. (February 2014) - Park, Yong Bum; Kim, Changhwan; Hwang, Yong Il; Lee, Chang Lyul; Lee, Won-Yeon; Park, Hye Yun; Heo, Jin Won; Lee, Hyun Kyung; Cho, Jae Hwa; Kwon, Yong Soo; Jung, Ji Ye; Juhn, Young J.; et al.
Abstract Objective: Previous studies reported that the most common chronic condition found among hospitalized patients due to the novel 2009 H1N1 influenza was asthma. However, these studies did not include a concurrent control group. Thus, we investigated the association of asthma status and severity of H1N1 influenza in adults. Methods: The study was designed as a multi-site case-control study. Cases were patients who had positive PCR for H1N1 influenza and were admitted to the ICU or general ward with a diagnosis of H1N1 influenza from 1 January 2009 to 31 December 2009. Controls were patients who had positive PCR for H1N1 influenza, but were not admitted to hospitals. Results: There were 91 H1N1 cases admitted to either ICU (n = 41) or general hospital ward (n = 50), and 56 controls who met the matching criteria were available. Of the 91 cases, the mean age was 47.3 years, 59% were female, and 38% had comorbid conditions. Of the 91 cases, 12 (13%) had asthma. Stratified analysis by comorbid conditions showed that among those without any comorbid conditions, 8 of 56 cases (14%) and 2 of 49 controls (4%) had asthma, (OR: 3.92, 95% CI: 0.79–19.42, p = 0.095) whereas, among the 39 subjects with one or more comorbid conditions, one of 7 controls (14%) had asthma and 4 of 35 (11%) cases had asthma (p = 0.83). Conclusions: Asthma may be associated with severity of H1N1 influenza among those without any non-asthma comorbid conditions. However, the limited sample size did not allow this study to fully establish statistical significance. We still recommend asthmatics as a priority group for influenza vaccination and treatment.